The science of starving in Victorian literature, medicine, and political economy - Mangham, Andrew (Oxford University Press, 2020)
The Science of Starving in Victorian Literature, Medicine, and Political Economy is a reassessment of the languages and methodologies used, throughout the nineteenth century, for discussing extreme hunger in Britain. Set against the providentialism of conservative political economy, this study uncovers an emerging, dynamic way of describing literal starvation in medicine and physiology. No longer seen as a divine punishment for individual failings, starvation became, in the human sciences, a pathology whose horrific symptoms registered failings of state and statute. Providing new and historically-rich readings of the works of Charles Kingsley, Elizabeth Gaskell, and Charles Dickens, this book suggests that the realism we have come to associate with Victorian social problem fiction learned a vast amount from the empirical, materialist objectives of the medical sciences and that, within the mechanics of these intersections, we find important re-examinations of how we might think about this ongoing humanitarian issue
Keywords: Hunger in literature / 19th century; Literature and medicine / 19th century; Medicine in literature / 19th century; English literature / 19th century / History and criticism; Starvation / 19th century; English literature; Hunger in literature; Literature and medicine; Medicine in literature; Starvation; 1800-1899; Criticism; interpretation; etc; Hunger; Verhungern; Englisch; Politische Ökonomie; Literatur; Medizin